THE TEACHERS’ USE OF MOTIVATIONAL STRATEGIES IN TEACHING ENGLISH AT SMA SWASTA IMELDA MEDAN - Tiffanny Tiffanny; Marisi Debora (Universitas Negeri Medan, 2022)
This research was aimed to describe the kinds of motivational strategies used by the teachers in teaching English at SMA Swasta Imelda Medan and the ways how the teachers apply the motivational strategies. In this research, the researcher used descriptive qualitative research design and involved two techniques of collecting data, they are: observation by observing the learning and teaching process, then took a note for getting the results which were related to the kinds of motivational strategies used by the teachers; and interview by asking the English teachers some questions related to the ways how the teachers apply the motivational strategies. The data gathered were processed in some stages in the form of data condensation, data display and drawing conclusion. The participants of this research were two English teachers of SMA Swasta Imelda Medan and 29 twelfth grade students. The result of this study showed that the first teacher applied 14 kinds of motivational strategies and the second teacher applied 16 kinds of motivational strategies. All of the strategies can be grouped into four aspects of MTP framework based on Dornyei’s theory and the ways how the teachers apply the strategies in those aspects were various, but similar. For creating basic motivational condition aspect, the teachers tried to create a proper good behavior and good relationship toward the students by greeting them cheerfully, showed enthusiasm, and asked how the students were doing. Then, in generating initial motivation aspect, the teachers always checked the students’ work to make sure there was no any obstacle and keep to asking the students’ understanding to the learning material. Next, for maintaining and protecting motivation aspect, the teachers presented task in a motivating way by giving the students opportunities to choose their own topics for the task and exercise. Finally, for encouraging positive retrospective self-evaluation aspect, the teachers gave a good feedback to the students by praising them and giving comment to their works.Keywords: Teachers’ Motivational Strategies, Students’ Motivation, MTP Framework.